Is neonatal phototherapy associated with a greater risk of childhood cancers? - Fatemeh Sabzevari; Reza Sinaei; Bahareh Bahmanbijari; Simin Dehghan Krooki; Azam Dehghani (BMC, 2022)
Abstract Background Neonatal phototherapy (NNPT) has long been used as an effective and relatively safe method of treating neonatal hyperbilirubinemia. Considering the subsequent evidence of long-term impacts of NNPT such as malignancies, this study was conducted to evaluate the relationship between NNPT and childhood cancers. Methods This case-control study assessed 116 children up to 4 years old with every kind of cancer referred to the Oncology department of Afzalipour hospital, Kerman, Iran, from 2011 to 18. Moreover, 116 pediatric patients without cancer hospitalized at the same Center were included after sex and age matching as the control group. The history of phototherapy and its duration were evaluated in these two groups. Results We found no association between the NNPT and malignancies in children. However, high intensive phototherapy was higher historically among affected cancerous patients than in non-cancerous cases without any statistically significant difference (25% vs 19%; P = 0.26). Maternal educational level and history of maternal infection during pregnancy, which initially appeared to be two factors associated with malignancy in single variable regression analyses, were not significant based on the adjusted models. Conclusions The results did not show a positive correlation between NNPT and childhood cancers, which may partly be due to the relatively small sample size of the study. However, some other evidence is worrisome enough that NNPT should not be considered risk-free. Additional multi-centric studies should be undertaken to specify that phototherapy is really safe.